PENERAPAN SISTEM PENDUKUNG KEPUTUSAN (SPK) DENGAN MENGGUNAKAN METODE FUZZY AHP (ANALYTICAL HIERARCY PROCESS) SEBAGAI PENENTUAN PENERIMA BEASISWA PIP - Ahmad Al A Dhomul Aflahin; M. Ivan Ariful Fathoni; Festian Cindarbumi (LPPM Universitas Bina Bangsa, 2023)
Determining PIP scholarship recipients is a matter of multi-criteria decision making. For this problem, a decision support system (SPK) was built to determine PIP scholarship recipients using criteria including: family economic condition, average family income, and number of parental dependents. The method used in this problem is the Fuzzy AHP (Analytical Hierarchy Process) method. Based on the results of testing the decision support system using the Fuzzy AHP method, this research succeeded in determining students who were entitled to receive the PIP scholarship, where from all alternative PIP scholarship applicants, the final clusterization value was obtained as 25% of the alternatives were entitled to receive it and 75% of the alternatives were not entitled to receive it. Apart from that, this decision support system is dynamic in nature, where the system can handle changes or additions to criteria